Science and Quality Education for Sustainability Development in Libya - Mahmoud M., Dboba; W., Astiata; S.P., Bindra (INTI International University, 2022)
The Paper is designed to present an overview on the state of art on new and emerging education and training approaches and methodologies to meet the sustainable development demands at global, regional, national, and local levels. It demonstrates that how crisis-ridden Libya is planning the vital role for effective education and training in chemical, biological, environmental science and engineering education using best practice blended learning approaches envisaged in United Nations Commission for Sustainable Development (UNCSD) Rio+20 Future We Want 2012 Report, United Nations Sustainable Development Goals (UN SDGs) 2015-30, 17 goals and 169 targets and Higher Education Sustainability Initiative (HESI) that help play in leveling the varied content knowledge, expertise and experience of professionals. It highlights a strategy and plan of action to meet the challenges of change and development in education and training required to develop the vital skills and experience of sustainable development professionals needed to perform their more sophisticated jobs with greater responsibility and accountability. Eventually, it provides a framework approach using outcomes, output, baseline, targets, performance indicators, and activities to design a wide range of formal education and training in chemical, biological, environmental protection science and engineering fields using new and emerging technologies for the enhancement of sustainable livelihood in Libya.